Using social network analysis to evaluate relationships among community nutrition education partners. (20th October 2021) - Kim, H; Zahng, L; Gold, A
Abstract: Background: The Supplemental Nutrition Assistance Program - Education (SNAP-Ed) program is an evidence-based program funded by the United States Department of Agriculture (USDA) that provides direct education and multi-level interventions for low-income families about nutrition, physical activity, and making healthy choices on a limited budget. Each U.S. state is funded to administer the program. SNAP-Ed works by building partnerships with community organizations. The purpose of this study was to identify characteristics of Minnesota's community partnership network involved in the SNAP-Ed program from the federal fiscal years 2016 (FY16) to 2020 (FY20). Analysis aims include 1) mapping the growth of SNAP-Ed community partners each year, 2) identifying essential network patterns and thereby highlight potential network gaps, 3) gauging the current level of partner involvement, and 4) enabling a data-driven approach for future collaborative network improvements. Methods: Social network theory and analysis (SNA) was used to examine changes in partnerships over time. The data was retrieved from Minnesota's SNAP Education Evaluation and Database System (SEEDS) where maintained program and evaluation data; SNA metrics such as size, breadth, density, degree centralization, clusters, and modularity were calculated for each network. Results: Partners of SNAP-Ed programs expanded from 869 in FY16 to 1032 in FY19. Due to COVID-19, in FY20, the number of partners decreased to 804. The network density decreased over time due to expansion of the number of partners between FY16(.0263) and FY19(.021). In FY20, the network density significantly decreased to .001 since partners were not able to be connected to each other. Network centrality will also be reported. Conclusions: Our study presents a novel use of social network analysis methods to evaluate the community partnerships involved in the SNAP-Ed program. Key messages: Using social network analysis to analyze the quantity and quality of the relationship among community nutrition education program partners gives practical policy recommendations. A novel use of social network analysis methods to evaluate the community partnerships involved in the SNAP-Ed program.